The Association between the History of HIV Diagnosis and Oral Health. (November 2016) - Burger-Calderon, R.; Smith, J.S.; Ramsey, K.J.; ,; Webster-Cyriaque, J.
Unmet oral care needs are high among people living with human immunodeficiency virus (HIV)/AIDS (PLWH). Oral health care is of increasing importance as life expectancy is being prolonged extensively among PLWH. The benefit of oral health care in relation to time since HIV diagnosis has not previously been assessed. A retrospective multivariable analysis of the Special Project of National Significance Oral Health Initiative observational cohort study ( N = 2, 178) was performed to estimate the odds ratios (ORs) of oral health outcomes comparing historically diagnosed subjects (>1 y since HIV diagnosis) to newly diagnosed subjects (≤1 y since HIV diagnosis). ORs were adjusted for age, study site, language, income, last dental care visit, and dental insurance. Historically diagnosed subjects were more likely to report oral problems than newly HIV-diagnosed subjects (OR, 2.10). Historically diagnosed subjects were more likely to require oral surgery (OR, 1.52), restorative treatment (OR, 1.35), endodontic treatment (OR, 1.63), and more than 10 oral clinic visits over the 24-mo study period (OR, 2.02). The crude cumulative 2-y risk of requiring prosthetic (risk difference [RD], 0.21) and endodontic (RD, 0.11) treatment was higher among historically than newly diagnosed subjects, despite no significance postadjustment. Furthermore, poor oral health outcomes were exacerbated among non–highly active antiretroviral therapy users. Summarizing, the authors found that historically diagnosed subjects were more likely to report oral problems and require dental procedures compared with newly diagnosed subjects, suggesting that oral health among PLWH declines over time since HIV diagnosis. Hence, newly diagnosed PLWH may benefit from the implementation of early oral interventions.